PLANNING AND DESIGN OF MODERN COTTAGE DARUL MADANI GONTOR 14 BATAM - Hutapea, Franki Erwanto; Parayogi, Laras Mitra; Karmawan, Septy; Ridwan, Muhammad Afif; Kusmawan, Edi; Riski, Despitra (JURNAL DIMENSI, 2023)
ABSTRACT The city of Batam is one of the cities in the Riau Archipelago Province which has a vision, namely the Realization of Batam as a Modern and Prosperous Civil World Airport, Bandar which means a city and Madani which means Civilized. Apart from being known as the Industrial City of Batam City, it is also called Bandar Madani. not only a nickname but also has the meaning of the development of the City of Batam directed at realizing a society with character, courtesy, discipline, and high culture in direct proportion to the concept of a religious civil society. Through this vision of the City of Batam, education and teaching facilities are urgently needed that shape human beings with character, civilized and religious, namely through Islamic boarding schools with the concept of modern building design as an image of modern civilization starting with modern building materials, building facades, as well as space requirements, facilities modern education such as laboratories, sports facilities to support the education and teaching process in modern Islamic boarding schools, as well as with a few touches of Malay architecture from the shape of the roof of the facade model of a Malay house building that has a light impression as local wisdom as outlined in the design concept, and with a bioclimatic concept approach as a response to the local climate. in the arrangement of building masses with a grid pattern and linear circulation in response to the Site Analysis. this is intended to present the physical appearance of modern Islamic boarding schools as character education facilities based on Islamic boarding schools with the concept of modern buildings with several architectural analogies of Malay house buildings as local wisdom for the people of Batam City in particular and the people of the Riau Islands in general. Keywords: Modern Boarding School.Madani.Modern Architecture.
Keywords: Modern Boarding School.Madani.Modern Architecture.